Hybrid Energy Harvesters (HEHs)-A Review - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2017)
In this millennium, the methodologies to harvest existing dissipated powers not only supply input energy to our sophisticated devices, but also contribute the current technological researches and developments. Single harvester generator or harvesting single power source may remain insufficient for the energy feed into the systems like electronic devices, biosensors, human, structural and machine health monitoring, and wireless sensor nodes. To overcome this problem, hybridization of energy harvesters (EHs) takes place to increase the limited energy generation of stand-alone EHs. In this chapter, piezoelectric and electromagnetic generators are compared and classic as well as novel hybrid energy harvester (HEH) designs are reviewed by considering fixed-frequency; broadband including linear, nonlinear and tunable HEHs; multimode; and multisource powered configurations. This review covers two-, three-, four-multi source powered HEHs in micro-, meso- and large-scales. Overall comparisons of classic and novel HEHs are tabulated and discussed in detail in order to guide potential researchers. In the scope of this chapter review, it is seen that HEHs generate greater power outputs than its single harvester components. The most promising power and energy generations are 315 mW by four-source powered novel HEH in meso-scale, 215 mu W by tunable broadband classic HEH in microscale and 440 kW h/day by partially three-source powered HEH in large scale. This chapter indicates that HEHs not only increase the output powers and power densities, but also enables endless configurations to maximize harnessing existing power sources.
Keywords: Hybrid energy harvesting; Multimode energy harvesting; Multisource energy harvesting; Novel energy harvesters; Microscale energy harvesting; Large-scale energy harvesting; POWER; WIND; SOLAR